Crop production potential of reclaimed mine sites for sustainable livelihoods - Tiimub, Benjamin Makimilua; Christophé, Niyungeko; Atepre, Bernice Awusi; Tiimob, Richard Wonnsibe; Tiimob, Gideon Lakida; Tiimob, Elisha Nyannube; Baani, Isaac; Amihere-Ackah, Paul; Agyenta, Joan Jackline (Goodwood Publishing, 2023)
Purpose: Potentiality of six reclaimed mine sites for crop production at Goldfields Ghana Limited, Tarkwa Mine was holistically assessed. Research methodology: Soil pH was traced using HI 9017 microprocessor meter while total nitrogen (TN), organic matter (OM) and organic carbon (OC) were determined by Kjeldahl digestion, distillation and Walkley-Black Methods. Calcium (Ca), magnesium (Mg), potassium(K), sodium (Na), were further determined in 1.0 M ammonium acetate (NH4OAc) extract, using hydrogen and aluminum in 1.0 M KCl, by EDTA titration and flame photometry. Results: Optimum soil pH, compared with other parameters down the trend was less than 4.33. In cmolkg-1, OM at Ajopa natural forest soil (2.52) was greater than West Heap (2.08). TN differed significantly (p ? 0.001) such that, Ajopa natural forest (0.13%) was greater than West Heap (0.11%). West Heap Ca (3.52) was greater than Bridge Dump Ground (BDG’s) (1.78) while Mg (1.25) at BDG was greater than West Heap (1.22). West Heap’s K (0.16) was greater than BDG’s (0.13). Sodium was entirely low (< 5 %). But acidity of Ajopa natural forest (1.90) was greater than BDG’s (1.89) while effective cation exchange capacity (ECEC) of West Heap (5.95) was greater than BDG’s (4.68). Conclusions: The study assessed reclaimed mine soils in Tarkwa, Ghana. Findings show highly acidic pH and low nutrients, limiting crop productivity. Soil improvement with lime, organic matter, and suitable crops is required for sustainable livelihoods. Limitation: Study sites sparsely located and require more experience to locate sampling points. Contribution: Analyses clearly revealed poor agglomeration of cation exchange capacities due to inadequate fertility of the seven-year old reclaimed mine sites. Hence, it may not give good crop yields for sustainable economic livelihoods strategies without long-term augmented fertilization and liming.